Resveratrol Prevents Campylobacter jejuni-Induced Leaky gut by Restoring Occludin and Claudin-5 in the Paracellular Leak Pathway - Lobo de Sá, F. D.; Heimesaat, M. M.; Bereswill, S.; Nattramilarasu, P. K.; Schulzke, J. D.; Bücker, R. (Frontiers in Pharmacology, 2021)
Campylobacter jejuni is a bacterial human pathogen causing gastroenteritis and sequelae like irritable bowel syndrome. Epidemiologists count the human campylobacteriosis by C. jejuni as the most common foodborne zoonosis and bacterial diarrheal disease worldwide. Based on bioinformatics predictions for potential protective compounds in campylobacteriosis, the question was raised whether the plant-based polyphenol resveratrol is sufficient to attenuate intestinal epithelial damage induced by C. jejuni. We investigated this by performing experimental infection studies in an epithelial cell culture and the secondary abiotic IL-10-/- mouse model. In C. jejuni-infected human colonic HT-29/B6 cell monolayers, transepithelial electrical resistance (TER) was decreased and the paracellular marker flux of fluorescein (332 Da) increased. Concomitantly, the tight junction (TJ) proteins occludin and claudin-5 were re-distributed off the TJ domain. This was accompanied by an increased induction of epithelial apoptosis, both changes contributing to compromised barrier function and the opening of the leak pathway induced by C. jejuni. In parallel, the recovery experiments with the application of resveratrol revealed a functional improvement of the disturbed epithelial barrier in both models in vitro and in vivo. During treatment with resveratrol, TJ localization of occludin and claudin-5 was fully in the paracellular domain of HT-29/B6 cells. Moreover, resveratrol decreased the rate of epithelial apoptosis. These resveratrol-induced molecular and cellular effects would therefore be expected to improve epithelial barrier function, thereby minimizing the so-called leaky gut phenomenon. In conclusion, the induction of the leak pathway by C. jejuni and the restoration of barrier function by resveratrol demonstrates its effectiveness as a potential preventive or therapeutic method of mitigating the leaky gut associated with campylobacteriosis.